Persepsi risiko terhadap minat melakukan pinjaman online dengan kemudahan penggunaan sebagai variabel moderasi - Uke Prajogo; Rusno Rusno (MBR (Management and Business Review), 2022)
This study aims to analyze and prove the effect of perceived risk on interest in making online loans with perceived ease of use as a moderating variable. The object of research is students who are members of ABM Preneur. Using primary data obtained through the distribution of online questionnaires. The sampling method is stratified purposive random sampling. The research findings reveal that the perception of risk does not affect the interest in making online loans, besides that the perception of ease of use is not able to moderate the influence of risk perceptions and interest in making online loans. Recommendations for further research are online loan trust in interest with information quality as a moderating variable